2020
DOI: 10.48550/arxiv.2009.07125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A functorial characterization of von Neumann entropy

Abstract: We classify the von Neumann entropy as a certain concave functor from finitedimensional non-commutative probability spaces and state-preserving * -homomorphisms to real numbers. This is made precise by first showing that the category of non-commutative probability spaces has the structure of a Grothendieck fibration with a fiberwise convex structure. The entropy difference associated to a * -homomorphism between probability spaces is shown to be a functor from this fibration to another one involving the real n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…And since the Hilbert-Schmidt adjoint of the partial trace is a * -homomorphism, the information discrepancy in this case coincides with the "entropy change along a * -homomorphism" defined in Ref. [70].…”
Section: Deterministic Evolutionsupporting
confidence: 67%
See 2 more Smart Citations
“…And since the Hilbert-Schmidt adjoint of the partial trace is a * -homomorphism, the information discrepancy in this case coincides with the "entropy change along a * -homomorphism" defined in Ref. [70].…”
Section: Deterministic Evolutionsupporting
confidence: 67%
“…The third equality follows from Theorem 5.1, while the remaining equalities follow from the previously computed identities as well as basic properties of the logarithm and the von Neumann entropy [70]. ■…”
Section: Extending Von Neumann Entropy To Quasi-density Matricesmentioning
confidence: 85%
See 1 more Smart Citation
“…There have been other categorical approaches to entropy, most notably [BFL11], [BF14], [Lei21], and [Par22]. Our presentation here has almost nothing in common with those.…”
Section: Introductionmentioning
confidence: 85%
“…perspective and showed that so-called information functions of degree 1 behave "a lot like certain derivations" [EVG15]. A few years prior in 2011, Baez, Fritz, and Leinster gave a category theoretical characterization of entropy in [BFL11], which was recently extended to the quantum setting by Parzygnat in [Par20]. In preparation of that 2011 result, Baez remarked in the informal article [Bae11] that entropy appears to behave like a derivation in a certain operadic context, an observation we verify and make explicit below.…”
Section: Introductionmentioning
confidence: 99%